Additional file 4 of Revisiting chloroplast genomic landscape and annotation towards comparative chloroplast genomes of Rhamnaceae - Kwanjeera Wanichthanarak; Intawat Nookaew; Phongthana Pasookhush; Thidathip Wongsurawat; Piroon Jenjaroenpun; Namkhang Leeratsuwan; Songsak Wattanachaisaereekul; Wonnop Visessanguan; Yongyut Sirivatanauksorn; Narong Nuntasaen; Chutima Kuhakarn; Vichai Reutrakul; et al. (My University, 2023)
Additional file 4: Table S6. SSRs of 25 Rhamnaceae chloroplast genomes.
Keywords: Rhamnaceae; Genomics and Phylogenetic Studies